The Impact of COVID-19 Pandemic Lockdown on the Incidence of New-Onset Type 1 Diabetes and Ketoacidosis Among Saudi Children - Alaqeel, Aqeel; Aljuraibah, Fahad; Alsuhaibani, Mohammed; Huneif, Mohammed; Alsaheel, Abdulhameed; Dubayee, Mohammad Al; Alsaedi, Abdulaziz; Bakkar, Ayman; Alnahari, Ahmed; Taha, Areej; Alharbi, Khulood; Alanazi, Yousef; et al. (Frontiers in Endocrinology, 2021)
Background: Overburdened healthcare systems during the coronavirus disease (COVID-19) pandemic led to suboptimal chronic disease management, including that of pediatric type 1 diabetes mellitus (T1DM). The pandemic also caused delayed detection of new-onset diabetes in children; this increased the risk and severity of diabetic ketoacidosis (DKA). We therefore investigated the incidence of new-onset pediatric T1DM and DKA in Saudi Arabia during the COVID-19 pandemic and compared it to the same period in 2019. Methods: We conducted a multicenter retrospective cohort study, including patients aged 1–14 years admitted with new-onset T1DM or DKA during the COVID-19 pandemic (March–June 2020) and the same period in 2019. We assessed factors including age, sex, anthropometric measures, nationality, duration of diabetes, diabetes management, HbA1c levels, glycemic control, cause of admission, blood gas levels, etiology of DKA, DKA complications, length of hospital stay, and COVID-19 test status. Result: During the lockdown, 106 children, compared with 154 in 2019, were admitted to 6 pediatric diabetes centers. Among the admissions, DKA was higher in 2020 than in 2019 (83% vs. 73%; P=0.05; risk ratio=1.15; 95% confidence interval, 1.04–1.26), after adjusting for age and sex. DKA incidence among new-onset T1DM and HbA1c levels at diagnosis were higher in 2020 than in 2019 (26% vs. 13.4% [P=<0.0] and 12.1±0.2 vs. 10.8±0.2.5 [P<0.001], respectively). Females and older patients had a higher risk of DKA. Conclusion: The lockdown implemented in Saudi Arabia has significantly impacted children with T1DM and led to an increased DKA incidence, including children with new-onset T1DM, potentially owing to delayed presentation.